Strategi Komunikasi Interpersonal Customer Service Bengkel Two Motor Sport Dalam Meningkatkan Kepuasan Pelanggan - Nursadrina, Dzakiyyah; Lancia, Ferrari; Achir , Andi Banus (Jurnal Sosial Teknologi, 2025)
This study analyzes the interpersonal communication strategies implemented by Two Motor Sport's customer service team to improve customer satisfaction. The main focus of this study is interpersonal communication conducted online (via digital media) and offline (in-person). Using a descriptive qualitative approach with a constructivist paradigm, which views interaction as a process of building relationships between companies and customers. Data were collected through interviews with the owner, customer service, and company customers, and direct observation at the company. The results of the study indicate that customer service implements interpersonal communication strategies including openness, empathy, support, positive attitudes, and equality in interactions. Facial expressions, eye contact, voice intonation, and body gestures are symbols of offline (in-person) interactions, while online interactions focus on response speed, information accuracy, and the use of emojis, images, stickers, and friendly language as forms of symbolic interaction. Integration between offline and online interactions is an effective strategy in improving customer satisfaction. Customers feel valued, heard, and well-served, thus encouraging loyalty and potential repeat purchases. In addition, the role of customer service as a bridge between the company and customers successfully creates a positive image of the company. This study concludes that a well-executed interpersonal communication strategy can create a pleasant experience and increase a company's competitive value in the competitive automotive repair business.